Evaluation of the influence of polymorphisms of the transporter genes (RFC1, MDR1) and GGH on the efficacy of methotrexate in rheumatoid arthritis - I. V. Devald; E. A. Hodus; D. Yu. Nokhrin; E. B. Khromova; G. L. Ignatova; D. S. Stashkevich; A. M. Lila; A. L. Burmistrova (Современная ревматология, 2023)
The efficacy of methotrexate (MT) in patients with rheumatoid arthritis (RA) may be determined by genetic factors.Objective: to evaluate the isolated and combined effects of single nucleotide polymorphisms (SNPs) of membrane transporter proteins (RFC1 80G>A and MDR1 3435C>T) and the GGH -401C>T gamma-glutamyl hydrolase enzyme genes on the efficacy of MT in patients with RA.Material and methods. The study group consisted of 85 patients with a confirmed diagnosis of RA, who received therapy with MT starting at 10 mg/week and increasing in dose to a maximum of 25 mg/week. Efficacy was assessed after six months of treatment using the dynamics of the DAS28 index, identifying patients who responded and those who did not respond to MT therapy.Genotyping of RFC1, MDR1 and GGH gene polymorphisms was performed by real-time polymerase chain reaction. Three different approaches were used to analyze the results: 1) analysis for each of the genes; 2) logistic regression; and 3) multifactor dimensionality reduction (MDR).Results and discussion. Single gene analysis was used to determine the most likely predictors of non-response to therapy: 1) for GGH-401C>T, TT genotype (odds ratio, OR 5.09; 95% confidence interval, C11.11—23.3); 2) forMDR13435C>T, the TT genotype (OR 2.38; 95% CI0.89-6.37); 3) for RFC180G>A, not - AA genotype (OR 1.87; 95% CI 0.93-3.76).The logistic regression model showed a significant effect of homozygous genotype GGH -401TT on the efficacy of MT with low sensitivity of the method. The multifactorial dimensionality reduction results show a significant synergistic effect of the MT transport genes (MDR1, RFC1) and the GGH enzyme encoding the conversion of MT to the elimination form.Conclusion. Using various statistical methods, the following results were obtained: Single gene analysis revealed the most likely predictors of nonresponse to MT therapy: GGH -401C>T - TT genotype, MDR1 3435C>T - TT genotype, RFC1 80G>A - not-AA genotype; the method of multiple logistic regression allowed to determine the significant effect of GGH -401ТТ genotype on the effect of the drug with a low sensitivity of the method; the isolated effect of polymorphisms is probably less pronounced than their combined effect on the effectiveness of MT. SNP synergism is a major contributor to the development of treatment resistance. MDR is a promising method that can be used in the future to assess the impact of SNPs.